PROMOTION OF INFORMATION LITERACY ABILITIES OF SECONDARY SCHOOL LEARNERS BY PHYSICS LABS - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article deals with the role of Physics labs in promoting information literacy abilities of secondary school learners. The methodological basis of research is inquiry-based learning. The article focuses on the second level of inquiry-based learning referred to Guided inquiry. According to the The article deals with the role of Physics labs in promoting information literacy abilities of secondary school learners. The methodological basis of research is inquiry-based learning. The article focuses on the third level of inquiry-based learning referred to Guided Inquiry. According to the Guided Inquiry, the problem and procedures of labs are predefined for students but the methods of analysis, communication and conclusions are not set and depend on the students. The research problem is formulated as a question: What are information literacy abilities of secondary schools learners and how are they determined by the guided physics experimental activity?Learners’ information literacy abilities are analyzed on the basis of Information literacy model ACRL (The Association of College and Research Libraries). According to this model, informationliteracy is based on five groups of information abilities: an ability to recognize the need for information; an ability to search appropriate resources effectively and identify relevant information; an ability to evaluate information; an ability to know why information should be used in an ethical manner, and an ability to store and manage the information.